Penerapan Konseling Individu dengan Teknik Self Control dalam Mengatasi Celebrity Worship, (Studi Kasus pada Klien “N” di Komunitas Kpopers Palembang): Penelitian - Shalma Davina Sulaiman; Zhila Jannati; Hartika Utami Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study examines the phenomenon of celebrity worship in the case of “N,” an 18-year-old female university student who is an active member of the K-Pop Event Palembang Community. Established in 2022, this community serves as a creative platform for K-pop enthusiasts in Palembang to express themselves through activities such as dance covers, random play dances, and festivals. The organization has both internal (Steering Committee and Organizing Committee) and external structures, with a vision to strengthen relationships among fans through inclusive events and a mission to foster a positive ecosystem encompassing education and creative economy development. The description of client “N” reveals a complex personal background. She is an only child of divorced parents, living with her grandmother and uncle in a densely populated area of Palembang. Her educational history—from elementary to senior high school—shows a continuous interest in K-pop culture that began during junior high school. Her social environment is limited, with most of her interactions occurring within the K-pop community, reflecting a pattern of social isolation. The study employed a qualitative case study approach, with data collected through in-depth interviews and observations. The findings indicate that client “N” exhibits a high level of celebrity worship, characterized by excessive interest in the personal lives of idols, intensive monitoring of news and social media content, collection of merchandise, emotional attachment, neglect of social relationships, and impulsive behavior. The A-B-C behavioral analysis confirmed that this obsessive pattern significantly affected her daily life, showing deeply rooted and dominant manifestations. The intervention focused on self-monitoring, self-evaluation, and self-reinforcement, integrated with Islamic values such as mujahadah an-nafs (self-restraint and control of desire). The results revealed a significant decrease in obsessive indicators, shifting from dominant pre-counseling patterns to more controlled post-counseling behaviors, accompanied by improved social interactions and adaptive thinking patterns. Data analysis using Robert K. Yin’s pattern-matching, explanation-building, and time-series techniques confirmed gradual positive changes, consistent with previous studies linking celebrity worship to mental maladaptation and supporting the effectiveness of self-control in behavioral modification. The study concludes that the self-control technique is effective as an early intervention method in Islamic counseling guidance. Recommendations include the routine application of self-monitoring for clients, mental health education within fan communities, and further research with a broader sample. These findings contribute to improving the psychological well-being of K-pop fan adolescents and provide practical implications for community-based counseling interventions.